American ginseng acutely regulates contractile function of rat heart - Jiang, Mao; Murias, Juan M.; Chrones, Tom; Sims, Stephen M.; Lui, Edmund; Noble, Earl G. (Frontiers in Pharmacology, 2014)
Chronic ginseng treatments have been purported to improve cardiac performance. However reports of acute administration of ginseng on cardiovascular function remain controversial and potential mechanisms are not clear. In this study, we examined effects of acute North American ginseng (Panax quinquefolius) administration on rat cardiac contractile function by using electrocardiogram (ECG), non-invasive blood pressure measurement (BP) and Langendorff isolated, spontaneously beating, perfused heart measurements (LP). Eight-week old male Sprague Dawley rats (n= 8 per group) were gavaged with a single dose of water-soluble American ginseng at 300 mg/kg body weight. Heart rate and blood pressure were measured prior to and at 1 and 24 hr after gavaging (ECG and BP). Additional groups were used for each time point for Langendorff measurements. Heart rate was significantly decreased (ECG: 1 hr: 6 ± 0.2%, 24 hr: 8 ± 0.3%; BP: 1 hr: 8.8 ± 0.2%, 24 hr: 13 ± 0.4% and LP: 1 hr: 22 ± 0.4%, 24 hr: 19 ± 0.4%) in rats treated with water-soluble ginseng compared with pre or control measures. An initial marked decrease in left ventricular developed pressure was observed in LP hearts but blood pressure changes were not observed in BP group. A direct inhibitory effect of North American ginseng was observed on cardiac contractile function in LP rats and on fluorescence measurement of intracellular calcium transient in freshly isolated cardiac myocytes when exposed to ginseng (1 µg/ml and 10 µg/ml). Collectively these data present evidence of depressed cardiac contractile function by acute administration of North American ginseng in rat. This acute reduction in cardiac contractile function appears to be intrinsic to the myocardium.